2014
DOI: 10.1590/1678-775720130568
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality of prescription by dental students

Abstract: ObjectiveThe main objective of this study was to evaluate changes in prescribing pattern of Dentistry students throughout academic course.MethodsA case of non-complicated dental extraction was presented to all students that had completed their pharmacology coursework (from 4th semester to the last semester). The students were grouped according to year of study and were asked to prescribe paracetamol for pain control. A maximal score of 5 points was calculated from three subscores for identification of professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 10 publications
0
23
0
1
Order By: Relevance
“…Properly completed prescriptions and rational drug prescribing are important factors in the quality of pharmacotherapy delivery. 9 The results of the present study showed that only 45.6% of last-year dental students at the Tabriz Faculty of Dentistry had high skill in terms of writing prescriptions. In a similar study, Rauniar et al 12 reported a moderate level of skill in writing prescriptions in 258 medical and dental students in Nepal.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Properly completed prescriptions and rational drug prescribing are important factors in the quality of pharmacotherapy delivery. 9 The results of the present study showed that only 45.6% of last-year dental students at the Tabriz Faculty of Dentistry had high skill in terms of writing prescriptions. In a similar study, Rauniar et al 12 reported a moderate level of skill in writing prescriptions in 258 medical and dental students in Nepal.…”
Section: Discussionmentioning
confidence: 53%
“…8 Since dentists need to write prescription as a part of their clinical dental practice, absence of sufficient education for students is an important matter that influences the quality of rational medical prescribing. 9 A previous analysis of prescriptions in public health units in Brazil showed that prescriptions usually contained abbreviations and/or illegible letters and often lacked information about mode of administration, the total quantity of the drug being prescribed, dosage/ posology, duration, and/or guidance about the proposed treatment. 10 Therefore, proper education in writing prescriptions during university courses and regular assessment of students on prescription writing skills seem to be necessary for minimizing related errors and enhancing prescribing skills in their future practice.…”
mentioning
confidence: 99%
“…9 When investigating the relation between students' knowledge and their study level there was a statistically significance difference between 5th year students compared to 4th, 6th and interns (p>0.05); in contradiction to the findings of Moura et al, who found that knowledge improve as the year level increase. 10 A reasonable explanation in our case can be due to 5th year students taking the course during the study period. While 4th year haven't taken the second pharmacology course and most probably 6th year and interns had forgotten the information they were taught.…”
Section: Discussionmentioning
confidence: 60%
“…Omissions in dental prescriptions were also detected in a study of the quality of drug prescriptions by students from two sections of an undergraduate dental course. The study concludes that there were improvements in prescriptions as students advanced in the course; however, faults remain that are specifically related to the use of prescribed drugs [30].…”
Section: Discussionmentioning
confidence: 88%